Locals’ Perceptions Towards English For Local Tourism Industry - Sulistyawati, Devy; Halili, Mohammad (Lingual Journal of Language and Culture; Vol 15 No 1 (2023): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2023.v15.i01.p03, 2023)
This research aims to study the locals’ perceptions towards English in association with the local tourism destination development. Since language and tourism are interwoven, the use of language is linked to the likelihood of its popularity or infamy. It is undeniable that Indonesia requires English in all tourism sectors. The problem is that Indonesian's English proficiency in general is still in the lowest position among the members of the MEA. This has become one of the obstacles to make local tourism sites more competitive in the international sphere. Recognizing the communities’ perceptions to English would be a meaningful step to advance the potentials of the local tourism destination. Therefore, two issues that this research is concerned about are: the locals’ perceptions and the problems that might pose if English were introduced. The descriptive qualitative method employed. This research is located in Langgher Dhatang, Dusun Pogag, Desa Palalang, Kec. Pakong, Kab. Pamekasan, Madura. We interviewed thirteen local people living around the location. The participants’ involvement decision was made based on the assumption that they will have a direct impact for its language planning. We designed a questionnaire in a Google Form to ask and marked the answers in accordance with the participants’ responses. The research shows various attitudes towards English: most of them (76,9%) believe that English is important for Langgher Dhatang. 15,4% of the participants who have no idea either English will have a positive impact or not for local tourism development. The rest (7,7%) sees that English is inconsequential to its promotion. The problems that could arise include a low level of motivation in learning (15,4%), a low level of education (69,2%), and the youth ignorance in tourism site development (7,7%).